Volatılıty Spıllovers from The Internatıonal Capıtal Inflows to Economıc Growth in Turkey - Arif Orçun Söylemez (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2017)
This paper empirically investigates the volatility interactions between the international capital inflows to Turkey and Turkish economic growth using the post-financial-liberalization era data. With an Extended Constant Conditional Correlation GARCH model, it is shown that there are volatility spillovers from the capital inflows to growth in Turkey. Some earlier studies in literature have already established a positive relationship between the capital inflows and economic growth in Turkey. According to their results, as the mean value of capital inflows to Turkey increases, so does the conditional mean value of Turkish economic growth. This study is important for it shows that as the volatility of capital inflows to Turkey increases, so does the volatility of Turkish economic growth.